Surah al-Kāfirūn dan Etika Inklusif Islam: Pembacaan Hermeneutika Double Movement Fazlur Rahman - Safitry, Rizqy Laili (Kuras Institute, 2025)
The phenomena of intolerance and religious radicalism in Indonesia reveal a persistent gap between the universal message of the Qur’an and certain contemporary religious practices. One Qur’anic text that is particularly relevant to this issue is QS. al-Kāfirūn [109]: 1–6, which is frequently invoked in debates on religious freedom and interfaith relations. This study employs a qualitative hermeneutical textual analysis grounded in Fazlur Rahman’s double movement framework to examine the surah by reconstructing its historical context (legal specifics), formulating its universal moral ideals, and recontextualizing these ideals in response to present-day religious challenges. The findings demonstrate that, in its historical setting, QS. al-Kāfirūn articulated a firm rejection of theological compromise with the polytheistic practices of the Quraysh, while at the level of universal meaning it affirms the principles of religious freedom and respect for difference. This study offers a novel contribution by systematically applying Fazlur Rahman’s double movement hermeneutics to QS. al-Kāfirūn in order to bridge classical exegetical insights with contemporary discourses on tolerance and human rights, an aspect that has received limited attention in previous scholarship. By doing so, the article not only highlights the continued social relevance of the surah but also contributes theoretically to Qur’anic hermeneutics by demonstrating how the double movement approach can function as a coherent model for articulating an inclusive Islamic theology that is both textually grounded and contextually responsive within Indonesia and the wider global context.